2007
DOI: 10.1021/ol701743c
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Salviasperanol

Abstract: The achiral enynone shown cyclized to produce a tricyclic dienone that was converted in six steps to (-)-salviasperanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Ad ivergent, elegant, and short synthesis of 10 members of the icetexane family of naturalp roducts hasb een achieved in four to nine steps from abundant (+ +)-carnosic acid, isolated from Rosmarinus officinalis.O ft hese icetexanes, (+ +)-salvicanol (12), (À)-cyclocoulterone (1), (À)-coulterone (22), (À)-obtusinoneD (36), and (À)-obtusinone E( 37)h aveb een synthesized for the first time. As traightforward, inexpensive, and efficient sequence, consistingo ft he methylation and hydrogenation of rosemary ethanol extracts enriched with carnosic acid and related congeners, has been developedt oo btain the desired trimethyl carnosic acid 8 in high yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ad ivergent, elegant, and short synthesis of 10 members of the icetexane family of naturalp roducts hasb een achieved in four to nine steps from abundant (+ +)-carnosic acid, isolated from Rosmarinus officinalis.O ft hese icetexanes, (+ +)-salvicanol (12), (À)-cyclocoulterone (1), (À)-coulterone (22), (À)-obtusinoneD (36), and (À)-obtusinone E( 37)h aveb een synthesized for the first time. As traightforward, inexpensive, and efficient sequence, consistingo ft he methylation and hydrogenation of rosemary ethanol extracts enriched with carnosic acid and related congeners, has been developedt oo btain the desired trimethyl carnosic acid 8 in high yield.…”
Section: Discussionmentioning
confidence: 99%
“…Majetich and Zou have already reported such as ynthesis of brussonol( 33)f rom 31 through the heating of ac oncentrated solution of 31 in Et 2 O( 60 8C, 40 h, 70 %). [22] Furthermore, the crucial role of silica gel was further substantiated experimentally when an acetonitrile or acetone solutiono fb russonol (33)w as stirred under oxygen atmosphere and only trace amountso fp rzewalskin E( 32)w ere obtaineda fter several days. [30b] However,n one of thesemethods was suitable for producing przewalskin E( 32)d irectly from 31.…”
Section: Synthesis Of Members Of the Barbatusol Class Natural Productsmentioning
confidence: 99%
“…Somfai’s synthesis of anisomycin ( 51 ) 33 featured a vinylaziridine–pyrroline rearrangement. Njardarson’s synthesis of biotin ( 52 ) 34 featured a vinylthiirane–dihydrothiophene rearrangement, whereas salviasperanol ( 53 ) 35 was prepared by Majetich via vinyloxirane–dihydrofuran rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Majetich and co-workers also reported the first asymmetric total synthesis of (-)-salviasperanol in late 2007 (Scheme 17). 80 Vinylogous ester 137 was reacted with lithium acetylide, and treatment of the resulting adduct with aqueous HCl provided enynone 138. Although a cyclialkylation of 138 to dienone 140 could be envisioned, Drieding models of this species indicated that the arene and alkyne moieties were not close enough to react, and in the event 138 could not be directly converted to 140.…”
Section: Approaches To Barbatusol and Related Compoundsmentioning
confidence: 99%
“…89 Vinylogous ester 183 was converted to enynone 184 by treatment with Aren's reagent and subsequent acidic workup. As noted for the related enynone employed in the total synthesis of salviasperanol by Majetich et al (see Scheme 17), 80 direct cyclialkylation of 184 is not achievable due to the lack of proximity of the arene and alkyne moieties. However, Lindlar hydrogenation of 184 provided an intermediate dienone that was readily transformed to tricyclic dienone 185 on treatment with TiCl 4 or BF 3 $OEt 2 .…”
Section: Approaches To Coulterone and Related Compoundsmentioning
confidence: 99%